2007
DOI: 10.1002/chem.200601358
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Modeling of Enantioselective Pybox–Ruthenium‐ and Box–Copper‐Catalyzed Cyclopropanation Reactions: Scope, Performance, and Applications to Ligand Design

Abstract: An extensive comparison of full-QM (B3LYP) and QM/MM (B3LYP:UFF) levels of theory has been made for two enantioselective catalytic systems, namely, Pybox-Ru and Box-Cu complexes, in the cyclopropanation of alkenes (ethylene and styrene) with methyl diazoacetate. The geometries of the key reaction intermediates and transition structures calculated at the QM/MM level are generally in satisfactory agreement with full-QM calculated geometries. More importantly, the relative energies calculated at the QM/MM level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 68 publications
3
42
0
Order By: Relevance
“…Thus, when the cyclopropanation reactions were catalyzed by the laponite-exchanged PhBox-Cu complex, in hexane or styrene, a complete reversal of the trans/cis diastereoselectivity (31:69) was observed, and even more interestingly, the major cis-cyclopropane obtained had the 5 opposite absolute configuration, with regard to homogeneous phase results. When reusing the catalyst in dichloromethane, similar selectivities as in solution were achieved, proving that the reversal in trans/cis and enantioselectivity in ciscyclopropanes was not a permanent effect but a consequence 10 of a tight interaction with the surface.…”
Section: Examples Of Clay Surface Effects On Enantioselectivitymentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, when the cyclopropanation reactions were catalyzed by the laponite-exchanged PhBox-Cu complex, in hexane or styrene, a complete reversal of the trans/cis diastereoselectivity (31:69) was observed, and even more interestingly, the major cis-cyclopropane obtained had the 5 opposite absolute configuration, with regard to homogeneous phase results. When reusing the catalyst in dichloromethane, similar selectivities as in solution were achieved, proving that the reversal in trans/cis and enantioselectivity in ciscyclopropanes was not a permanent effect but a consequence 10 of a tight interaction with the surface.…”
Section: Examples Of Clay Surface Effects On Enantioselectivitymentioning
confidence: 69%
“…They are characterized by the lack of long-range 10 crystalline order. Amorphous silicas consist of particles of 1-100 nm which can be discrete, aggregated (1-25 µm) or agglomerated in a 3D network (silica gel).…”
Section: Solid Supports With Regular Structure In the Nanoscalementioning
confidence: 99%
“…An extensive study on the importance of the nature of the support has been recently reported, confirming the need of having a lamellar anionic support to observe such surface 55 confinement effects. 10 A simple model has been proposed to explain those results, taking into account the known cyclopropanation reaction mechanism [11][12][13][14][15][16][17][18][19][20] and the strong ionpair interaction between the key copper-carbene intermediate and the support surface, as well as the steric constraints of the 60 catalytic complex. From that model we proposed the synthesis of chiral ligands without C 2 symmetry as a method to enhance the surface-complex proximity and hence the support-complex interaction, allowing the surface to effectively shield one face of the complex.…”
Section: Consequence the Isomer Cis-(1s2r) (4s) Was Preferably Obtamentioning
confidence: 99%
“…oxazolinylquinoline-copper complexes, which are much more rigid, leading to almost planar geometries. 14,29 In order to test this hypothesis, copper complexes of both isopropylsubstituted 39 C 2 -symmetric bis(oxazoline) (11) and azabis(oxazoline) (12) chiral ligands ( Figure 2) were used in the 30 same conditions. The corresponding results are gathered in Table 1 (entries 7 and 8).…”
mentioning
confidence: 99%
See 1 more Smart Citation